Silvopastoral systems and their role in climate change mitigation and nationally determined contributions in Latin America - Rivera, Julián Esteban; Serna, Laura; Arango, Jacobo; Barahona, Rolando; Murgueitio, Enrique; Torres, Felipe; Chará, Julián (Springer, 2023)
Cattle ranching is a productive activity that generates high amounts of greenhouse gases (GHG) such as methane (CH4), nitrous oxide (N2O) and carbon dioxide (CO2), but can also provide effective alternatives to mitigate and adapt to climate change. Within the livestock sector, silvopastoral systems (SPS) have the capacity to reduce GHG emissions, increase carbon stocks, adapt to climate change, improve animal welfare and increase production of milk, beef and timber under different conditions. This chapter seeks to identify relevant elements related to the capacity of SPSs and livestock in general to meet the Nationally Determined Contributions (NDCs) of Latin American countries, and how nations are incorporating these systems into their mitigation policies. Different research and experiences demonstrating the mitigation potential of SPSs are presented, as well as those elements that must be considered for a successful upscale of these technologies. It also demonstrates the versatility of SPSs and the need for these systems to be incorporated into the NDCs and contribute to their achievement. Countries such as Argentina, Brazil, Chile, Colombia, Costa Rica, Mexico, Paraguay, Uruguay, highlight the need to have mitigation options in livestock activities in order to achieve the objectives proposed in their NDCs, which aim at reductions above 30% of the inertial scenarios.